New developments in von Willebrand disease. (12th May 2020) - Fogarty, Helen; Doherty, Dearbhla; O'Donnell, James S.
Summary: Von Willebrand disease (VWD) constitutes the most common inherited human bleeding disorder. It is associated with a mucocutaneous bleeding phenotype that can significantly impact upon quality of life. Despite its prevalence and associated morbidity, the diagnosis and subclassification of VWD continue to pose significant clinical challenges. This is in part attributable to the fact that plasma von Willebrand factor (VWF) levels vary over a wide range in the normal population, together with the multiple different physiological functions played by VWF in vivo . Over recent years, substantial progress has been achieved in elucidating the biological roles of VWF. Significant advances have also been made into defining the pathophysiological mechanisms underpinning both quantitative and qualitative VWD. In particular, several new laboratory assays have been developed that enable more precise assessment of specific aspects of VWF activity. In the present review, we discuss these recent developments in the field of VWD diagnosis, and consider how these advances can impact upon clinical diagnostic algorithms for use in routine clinical practice. In addition, we review some important recent advances pertaining to the various treatment options available for managing patients with VWD.